Comparison of using distribution‐specific versus effective radius methods for hydrometeor single‐scattering properties for all‐sky microwave satellite radiance simulations with different microphysics parameterization schemes. Issue 13 (6th July 2017) - Sieron, Scott B.; Clothiaux, Eugene E.; Zhang, Fuqing; Lu, Yinghui; Otkin, Jason A.
Abstract: The Community Radiative Transfer Model (CRTM) presently uses one look‐up table (LUT) of cloud and precipitation single‐scattering properties at microwave frequencies, with which any particle size distribution may interface via effective radius. This may produce scattering properties insufficiently representative of the model output if the microphysics parameterization scheme particle size distribution mismatches that assumed in constructing the LUT, such as one being exponential and the other monodisperse, or assuming different particle bulk densities. The CRTM also assigns a 5 μm effective radius to all nonprecipitating clouds, an additional inconsistency. Brightness temperatures are calculated from 3 h convection‐permitting simulations of Hurricane Karl (2010) by the Weather Research and Forecasting model; each simulation uses one of three different microphysics schemes. For each microphysics scheme, a consistent cloud scattering LUT is constructed; the use of these LUTs produces differences in brightness temperature fields that would be better for analyzing and constraining microphysics schemes than using the CRTM LUT as‐released. Other LUTs are constructed which contain one of the known microphysics inconsistencies with the CRTM LUT as‐released, such as the bulk density of graupel, but are otherwise microphysics‐consistent; differences in brightness temperature to using an entirely microphysics‐consistent LUT further indicate the significance of that inconsistency. The CRTM LUT as‐released produces higher brightness temperature than using microphysics‐consistent LUTs. None of the LUTs can produce brightness temperatures that can match well to observations at all frequencies, which is likely due in part to the use of spherical particle scattering. Key Points: The CRTM is modified to use microwave scattering look‐up tables made consistent with cloud/precipitation properties of microphysics schemes The CRTM as‐released, using effective radius to specify cloud particle sizes, produces higher brightness temperatures than the modified CRTM Brightness temperatures are sensitive to the assumed bulk density of graupel and ice cloud particle sizes produced by microphysics schemes